Navigating the complexity of disability support in tertiary education: perspectives of students and disability service staff. Issue 8 (3rd August 2017) - Fossey, Ellie; Chaffey, Lisa; Venville, Annie; Ennals, Priscilla; Douglas, Jacinta; Bigby, Christine
ABSTRACT: Access to education is a right for all students. This right is typically realised through the provision of disability support and reasonable adjustments to enable tertiary students with disabilities to participate on an equal footing with their peers. This paper presents perspectives of disability service staff and students about implementing and using reasonable adjustments. Data were collected at 2 tertiary institutions in Australia through interviews with 25 students with disabilities and 7 disability service staff. Data were thematically analysed. The complexity of and variability in the processes of negotiating and implementing disability support were identified as an overarching theme in the data. These processes involved engaging multiple parties. The task of negotiating reasonable adjustments is used to illustrate some of the complexities inherent in supporting students with disabilities. These findings challenge existing assumptions that support is easily accessible and simply provided. They highlight the complexity of using reasonable adjustments, and the tendency for this to be seen as a student responsibility. Finally, the findings imply that disability services need to reorient from a focus on care and concern towards a rights orientation and foster students' skills in self-advocacy to better enable them to negotiate without disadvantage.